Modified L-Z-source inverter with high gain inversion and inductive load compatibility - Bussa V.K.; Singh R.K.; Mahanty R. (My University, 2025)
This paper proposes a modified L-Z-source inverter (L-ZSI), which is derived from L-ZSI with addition of few more elements to overcome the limitations of L-ZSI. The modified L-ZSI gives higher boosting capability at low shoot-through duty ratio and improved AC output voltage at reduced harmonic distortions unlike conventional L-ZSI. Due to its higher boosting capability at low duty ratio, it is appropriate to connect low input voltage sources to grid or standalone systems at reduced harmonic distortions. Detailed mathematical modelling is carried out and a scaled down laboratory prototype is developed to verify the performance of the proposed inverter. © 2018 IEEE.